Non-haemorrhagic causes of obstetrical intensive care unit admissions in tertiary care setting - Kamal, Preet; Kaur, Surinder; Kaur, Harleen; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Management of critically ill obstetric patients involve intensive monitoring in intensive care unit. In present scenario there are significant number of obstetric patients with sepsis, tropical diseases and medical illness that require ICU care. The aim of this study was to evaluate in more detail the non-haemorrhagic causes of obstetric ICU admissions and to identify and adopt high risk strategies as prime learning objective. Methods: It is a prospective ongoing study conducted in 50 patients in SGRDUHS, Amritsar from December 2016 to October 2019, who were admitted in obstetric ICU, out of them 30 cases were attributed to non-haemorrhagic obstetric causes. All demographic parameters along with gestational age, diagnosis on admission, intervention done prior to shift to ICU and details of treatment given in ICU were evaluated. Patient outcome, review of mortality and area of improvement were also noted. Results: Majority of the patient (70.1%) were admitted in 3rd trimester. Obstetric sepsis (13.33%), infective diseases (16.66%), tropical conditions (16.66%), medical disorders (26.66%) and hypertensive disorders (26.66%) were the major causes of admission to obstetric ICU. There were 33.3% mortalities observed in present study and 40% were due to respiratory failure. In ICU mechanical ventilation was done in 63.3% cases and blood products were given in 33.3% of patients. Conclusions: A multidisciplinary approach is ideal to handle non-haemorrhagic situations especially related to medical disorders and tropical diseases. Review of the ICU admissions and periodic audit can improve management of morbidities as well as reduce maternal mortalities.